1989
DOI: 10.1190/1.1442581
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of surface‐to‐borehole electromagnetic logging in cased holes

Abstract: A new electromagnetic logging method, in which the source is a horizontal loop coaxial with a cased drill hole and the secondary axial fields are measured at depth within the casing, has been analyzed. The analysis, which is for an idealized model of an infinite pipe in a conductive whole space, has shown that the casing and formation are uncoupled at the low frequencies that would be used in field studies. The field inside the casing may be found by first finding the field in the formation and then using this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 1 publication
6
34
1
Order By: Relevance
“…In this we agree with previous work on the casing problem done for other transmitter-receiver configurations (Augustin et al, 1989;Wu et al, 1994) where it was shown that the steel casing acts as a linear filter. Although it appears that the casing attenuation function is largely dependent on the casing induction parameter or its thickness/skin depth ratio, the formation signal can only be recovered properly if all the casing parameters are individually known with good accuracy.…”
Section: Conclusion and Recommendationssupporting
confidence: 93%
See 1 more Smart Citation
“…In this we agree with previous work on the casing problem done for other transmitter-receiver configurations (Augustin et al, 1989;Wu et al, 1994) where it was shown that the steel casing acts as a linear filter. Although it appears that the casing attenuation function is largely dependent on the casing induction parameter or its thickness/skin depth ratio, the formation signal can only be recovered properly if all the casing parameters are individually known with good accuracy.…”
Section: Conclusion and Recommendationssupporting
confidence: 93%
“…Results of previous theoretical work and numerical calculations by Augustin et al (1989), Uchida et al (1991) and Wu and Habashy (1994) all pointed to the possibility of extracting a formation signal from electromagnetic measurements through casing. In particular, the Augustin results showed that the casing acts as a strong low pass filter.…”
Section: Introductionmentioning
confidence: 92%
“…Wait & Hill (1973) considered a long vertical extended cylinder in a homogeneous halfspace. Augustin et al (1989) investigated how EM measurements could be carried out behind a metal casing.…”
Section: Introductionmentioning
confidence: 99%
“…(r) the electric permittivity, *(r) the magnetic permeability, and J,(r) the source current distribution expressed as (Augustin et al, 1989) where I(=) is the amount of the current impressed, and ( I is the radius of the current ring.…”
Section: Technical Descriptionmentioning
confidence: 99%